Paraguay : 2020 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Paraguay. (IMF Staff Country Reports; Country Report ;, 2021)
In the past two decades, Paraguay has seen strong growth and a sharp reduction in poverty. Strong GDP growth was the result of sound macro policies (with low inflation and low fiscal deficits and debt) and an agricultural commodity price boom which spilled over to the non-tradable sector. Growth was not just high but also volatile, as bad weather shocks led to poor harvests, which spill over to the broader economy. In early 2020, Paraguay was rebounding strongly from another weather shock, and full-year growth was forecast at over 4 percent. In 2019, bad weather had reduced the harvest, and GDP growth had come to a near standstill. A recovery started in the second half of 2019 and gathered strength in early 2020-in February economic activity was 7 percent higher than a year earlier. The Covid-19 epidemic halted the recovery. An early lockdown-which kept the death toll among the lowest in the region-led to a sharp contraction in economic activity, with April activity levels at 20 percent below those in February. Women, informal sector workers, and workers in the service sector were particularly hard hit; while children were severely affected by the closing of the schools until the end of 2020.